Manuskrip lama: asas keupayaan dan Kearifan Melayu Tradisi - Atikah Abd. Azam,; Othman Yatim, (Universiti Kebangsaan Malaysia, 2012)
Generally this article provides a brief overview of Malay manuscripts. Malay manuscript is considered to be one of the contributions of traditional Malay society who are able to produce ideas that can be utilised until now. The production of this manuscript reflects the ability of the creative community and basically its production also reflects the cultural life of the Malays of the past. In studying this situation, the introduction of a manuscript in general is really needed. It covers the physical picture and its content.